Hypogonadotropic Hypogonadism Associated with Hereditary Hemorrhagic Telengiectasia. (4th April 2013) - Valentina, Scarano; Daniele, De Santis; Patrizia, Suppressa; Patrizia, Lastella; Mariano, Lenato Gennaro; Vincenzo, Triggiani; Carlo, Sabbà
Abstract : A 65-year-old man was referred to our clinic for the rehabilitation of right hemiparesis caused by ischaemic stroke. Hypertension, postphlebitic syndrome of lower limbs, frequent nose bleeding, and anemia were present in his history; in his adolescence, he was treated for idiopathic hypogonadotropic hypogonadism. Further investigations have revealed also microsomia, suggesting a clinical diagnosis of Kallmann syndrome, that is, an association, possible in males and females, of hypogonadotropic hypogonadism with olfactory deficits. A definite diagnosis of hereditary hemorrhagic telangiectasia was made based on clinical criteria and confirmed by genetic analysis.